Kobieta jako materia comica – polski ślad nowołacińskiej publicystyki z przełomu XVI i XVII wieku - Gaj, Beata (Colloquia Litteraria, 2024)
This article addresses the issue of the use of female themes in Renaissance journalism with a religious argument. To exemplify the issue, several examples were selected from the New-Latin literature of Silesia during the formative period of the Reformation. The most obvious example of the use of female themes was a work (allegedly) proving that women are not human, which caused quite a stir in Europe. This treatise was attributed to Valens Acidalius, who, however, in letters to friends that are not widely known, points to a Polish trace of the dispute’s origins.